Translation, Adaptation and Validation of the "Cultural and Psychosocial Influences on Disability (CUPID) Questionnaire" for Use in Brazil Traducción, adaptación y validación del cuestionario Cultural and Psychosocial Influences on Disability (CUPID) para uso en Brasil Tradução, adaptação e validação do Cultural and Psychosocial Influences on Disability (CUPID) Questionnaire para uso no Brasil - Andrea Lepos Ferrari; Patricia Campos Pavan Baptista; Vanda Elisa Andres Felli; David Coggon (Universidade de São Paulo, 2010)
The paper describes the adaptation and testing of the Cultural and Psychosocial Influences on Disability Questionnaire for use in Portuguese. The cross-cultural adaptation followed the steps of translation, back-translation, evaluation of the translations by a committee of judges, and then piloting of the pre-final version. This was performed in a sample of 40 nursing staff from the Hospital at the University of São Paulo. Adjustments were made after review of the translations by the committee of judges (CVI≤ 80%). The pilot study was used to test whether questions could be satisfactorily understood and completed (≥ 85% of subjects). The Brazilian version of the Questionnaire is an adequate instrument for the ascertainment of occupational activities, psychosocial aspects of work, musculoskeletal symptoms and associated disabilities in nursing staff. El objetivo de este estudio fue describir la adaptación y validación del cuestionario Investigación Internacional sobre las Influencias Físicas, Culturales y Psicosociales en los Síntomas Musculares Esqueléticos e Incapacidades Asociadas, para la lengua portuguesa. El proceso de adaptación transcultural siguió las etapas de traducción, retrotraducción, evaluación de las traducciones por un comité de jueces y, en seguida, la realización de una prueba de la versión prefinal. Se utilizó una muestra de 40 trabajadores de enfermería del Hospital de la Universidad de Sao Paulo. Las adaptaciones fueron hechas después de someterlo al comité de jueces (IVC≤80%). La prueba piloto comprobó la comprensión de las preguntas a través del llenado (≥85% de los sujetos). La versión brasileña del cuestionario mostró ser un instrumento adecuado para la verificación de las actividades profesionales, aspectos psicosociales del trabajo y síntomas osteomusculares, asociados a incapacidad entre los trabajadores de enfermería. O objetivo deste estudo foi descrever a adaptação e validação do Questionário Pesquisa Internacional sobre as Influências Físicas, Culturais e Psicossociais nos Sintomas Musculoesqueléticos e Incapacidades Associadas, para a língua portuguesa. O processo de adaptação transcultural seguiu as etapas de tradução, retrotradução, avaliação das traduções por um comitê de juízes e, em seguida, teste da versão pré-final. Utilizou-se amostra de 40 trabalhadores de enfermagem do Hospital da Universidade de São Paulo. Adaptações foram feitas após a submissão ao comitê de juízes (IVC≤80%). O teste piloto testou a compreensão das questões pelo seu preenchimento (≥85% dos sujeitos). A versão brasileira do Questionário mostrou ser instrumento adequado para a verificação das atividades profissionais, aspectos psicossociais do trabalho e sintomas osteomusculares, associados à incapacidade entre os trabalhadores de enfermagem.